India-ASEAN-5 Economic Integration: Impact of Liberalization - Liew, Venus Khim-Sen; Lee, Huay-Huay; Lee, Hock-Ann (Icfai University Press, 2007)
Understanding the degree of integration between India and the Association of Southeast Asian Nations (ASEAN) is important to measure the impact of the proposed India-ASEAN Free Trade Area (FTA). If both India and ASEAN are well integrated, the impact of such liberalization will be small and vice versa. The Augmented Dickey-Fuller (ADF) and Phillips and Perron (PP) test results indicate that India and ASEAN are relatively integrated with respect to goods and services markets, but the Purchasing Power Parity (PPP) evidence is comparatively still a weaker one. Financial market integration, however, remains significantly incomplete. The main implication of this finding is that the impact of future liberalization will be great on financial markets. Due to the weak PPP evidence, the goods and services markets will also receive substantial impact from future liberalization. This suggests that the two regions could further exploit their partnership in FTA in their complementary areas, both in goods and services markets, and financial markets, in particular.